Photoinduced hydroxylperfluoroalkylation of styrenes. Issue 6 (18th January 2018) - Chen, Tongbi; Guo, Yong; Sun, Ke; Wu, Li-Zhu; Liu, Wen-Qiang; Liu, Chao; Huang, Yangen; Chen, Qing-Yun
Abstract : "No Catalyst is Better" is confirmed in the hydroxylperfluoroalkylation of styrenes with perfluoroalkyl iodides under irradiation by visible light. Abstract : A transition metal- and organophotocatalyst-free hydroxylperfluoroalkylation of styrenes under visible-light irradiation was developed. In this protocol, an electron donor–acceptor complex (perfluoroalkyl iodide and tertiary amine) was employed for the introduction of a perfluorinated chain and molecular oxygen was used as a green oxidant for the generation of hydroxyl groups. Various styrenes successfully undergo the reaction affording the corresponding fluorine-containing alcohols in up to 96% yields.